The Position of Customary Marriage in Australia and Indonesia: A Comparative Study of Aboriginal and Sunda Wiwitan Marriage Registration - Drajat, Muhammad Rifqi Rafi; Suparto, Susilowati (Universitas Labuhanbatu, 2025)
Australia and Indonesia have recognized the existence of indigenous peoples in their constitutions. However, in the implementation of marriage registration, there are still several obstacles that prevent registration. The research method used is empirical juridical, obtained directly through a study of the norms and principles contained in primary, secondary, and tertiary legal data. The results of the study indicate that the customary marriages of the Aboriginal indigenous community are still not fully recognized in Australia due to Australian marriage regulations that only recognize one marriage law, namely the Marriage Act 1961, with marriage ceremonies conducted formally before a marriage celebrant. Customary marriage practices conducted by the Aboriginal community cannot be registered by the state, while marriage registration for the Sunda Wiwitan indigenous community in Indonesia can be registered provided that the indigenous community has joined an organization registered under the Ministry. The legal consequences of marriages within the Sunda Wiwitan and Aboriginal communities will impact several aspects, including uncertainty regarding the legal status of children born from such marriages, difficulties in registering other administrative documents, and challenges in accessing public facilities provided by the government, particularly in the area of healthcare due to ongoing requirements.Keywords: Indigenous Peoples; Marriage Registration; Aboriginals; Sunda Wiwitan; Legal Recognition